A new simplified space-vector PWM method for three-level inverters. - Jae Hyeong Seo (IEEE Transactions on power electronics)
In this paper, a new simplified space-vector pulse width modulation (SVPWM) method for a three-level inverter is proposed. This method is based on the simplification of the space-vector diagram of a three-level inverter into that of a two-level inverter. If simplified by the proposed method, all the remaining procedures necessary for the three-level SVPWM are done like conventional two-level inverter and the execution time is greatly reduced. The DC-link neutral-point potential control algorithms are implemented more easily. The proposed method can be applied to the multi-level inverters above three-level. The validity of the new SVPWM method is verified by experiment with a 1000 kVA three-level insulated gate bipolar transistor (IGBT) inverter